Inclusive Sport and Education: Adapting Physical Activity for Children with Physical and Intellectual Disabilities (International Seven Journal of Multidisciplinary, 2023)
Inclusive sport and physical education play a fundamental role in promoting equity, health, and social participation among children with physical and intellectual disabilities. Beyond physical benefits, inclusive sports environments foster psychosocial development, self-esteem, autonomy, and a sense of belonging. This article discusses inclusive approaches to working with children with disabilities in sport and physical education contexts, combining evidence from academic literature with reflective practice based on professional experience. Emphasis is placed on pedagogical flexibility, environmental adaptation, individualized instruction, and peer support as key strategies for ensuring meaningful participation. By adapting activities, communication methods, and learning expectations, educators and coaches can create inclusive spaces where children with diverse abilities are empowered to develop not only athletic skills but also personal and social competencies. The article argues that inclusive sport is not merely a technical adjustment, but an ethical commitment to diversity, dignity, and equal opportunity in childhood development.